Formulation and of Commiphora caudata (Wight and Arn.) Engl.:- Herbal Wound Healing Ointment - Munde, Adinath Vishvanth; Pethappachetty, Palanisamy; Rakh, Maharudra Shamrao (Asian Journal of Biological and Life Sciences)
Aim: The present study explores compatibility studies, analysis, physiochemical parameters of formulated ointment with herbal wound healing ointment activity. Materials and Methods: Commiphora caudata bark ethanolic extract used to prepare ointment after studies different solvents phytoconstituents potential. Ethanolic extract of the bark of the Commiphora caudata was studies for its in vitro wound healing activity through scratch wound assay performed on 3T3-CCL92 cells. The rate of healing was examined at regular intervals and determined using ImageJ software. Results: The concentrations (50-1000 μg/mL) with the fibroblast cells (3T3-CCL92) caused a large spike in the proportion of wound healing activity levels ranging from 30.75%-59.15%. The percentage inhibitory concentrations, CTC50 values, for the wound healing concentration in fibroblast cells (3T3-CCL92) were calculated from the dose-response curve produced linear. The microscopic image represents increase the concentration of the plant extract result increase the wound healing activity linearily and also number of viable cells also increases. Conclusion: Commiphora caudata ethanolic extract shows the presence of majority of phytoconstituents as well the microscopic image represents increase the concentration of the plant extract result increase the wound healing activity linearly and also number of viable cells also increase.
Keywords: Commiphora caudata (Wight and Arn.) Engl.; Herbal Wound healing ointment; Cell Line - 3T3 - CCL92; In vitro Wound healing activity.